Investment Decision Making With Investment Satisfaction As An Intervening Variable: Availability Bias And Financial Literacy - Ira Wikartika; Ayundha Evanthi; Rahman Amrullah Suwaidi (Universitas Muhammadiyah Sidoarjo, 2023)
Good investment climate is expected to attract investors to invest their capital with the convenience offered. The role of investor behaviour is very important in the use of the capital market as a place to invest. Rational considerations and emotional aspects also influence investment decision making. Young investors tend to have an aggressive nature that is very influential on making investment decisions. Availability bias is the ease of obtaining information so that investors tend to make investment decisions based on the information that is most quickly obtained. Stock investment literacy for each individual has a different level and will influence decision making as a form of stock investment behaviour. This paper aims to analyse the effect of availability bias and investment literacy on the decision to invest in shares of young investors by using satisfaction as a mediating variable. The respondents of this research are young investors in Surabaya with a sample of 93 respondents and the data is analysed using PLS-SEM. The result of this research are only financial literacy which has a direct effect on investment satisfaction, and investment satisfaction is able to mediate the relationship between financial literacy and investment decision making on investors.